Measuring the Validity of Gharar from an Islamic Legal Perspective (Comparative Study of Gharar According to the Fuqaha) - Dodi Yarli; Sofyan Al-Hakim; Iwan Setiawan (al-Afkar, Journal For Islamic Studies, 2024)
. Gharar is one of the important concepts in Islamic law related to uncertainty or ambiguity in a transaction. This concept has a significant impact on the validity of a contract or contract in the context of finance and trade in sharia. Therefore, a deep understanding of gharar is essential in determining the halalness of a transaction. The aim of this research is to carry out a comparative study of the ulama's views on the concept of gharar. This research uses a qualitative approach method by collecting data through literature studies and analysis of the opinions of different scholars. Results show that the views of scholars on gharar have variations and differences that can be distinguished in several categories. One category is scholars who consider gharar to be something that should be avoided completely, and they tend to limit transactions that contain significant uncertainty. Meanwhile, there are also scholars who allow a certain level of gharar in transactions, provided that there are clear economic benefits and no fraud or injustice. In addition, the study also identified factors that influence the different views of scholars on gharar. These factors include an understanding of related sharia texts, historical and social contexts, and an understanding of the sharia goals to be achieved through the concept of gharar.